Retinal structure and related factors in 8-year-old Japanese children: The Yamanashi adjunct study of the Japan Environment and Children’s Study - Ryo Harada; Mingxue Bao; Natsuki Okabe; Yuka Kasai; Airi Takahashi; Chio Kuleshov; Yumi Shigemoto; Tadao Ooka; Hiroshi Yokomichi; Kunio Miyake; Reiji Kojima; Ryoji Shinohara; et al. (PLoS ONE, 2025)
Purpose The purpose of this study was to investigate the relationships among retinal/choroidal structures and associated factors in 8-year-old Japanese children who participated in the Yamanashi Adjunct Study of the Japan Environment and Children’s Study (JECS). Methods This was a study of 557 8-year-old Japanese children (274 boys, 283 girls) who participated in the JECS at the University of Yamanashi from June 2021 to March 2022. The visual acuity, spherical equivalent (SE), axial length (AL), and body height of the participants were measured. Retinal and choroidal thickness were measured using spectral domain optical coherence tomography (NIDEK RS-3000 Advance, Gamagori, Japan). Results This study included 304 participants (150 boysand 154 girls). The mean values were 23.08 ± 0.75mm for AL, −0.35 ± 0.79D for SE, and 0.08 ± 0.20 for uncorrected logMAR.The mean retinal thickness was 309.7 ± 10.9µm for all retinal layers (ARLs), 220.9 ± 15.3µm for the fovea, 134.8 ± 6.8µm for the outer retina, 76.1 ± 4.5µm for the inner retina, and 29.1 ± 2.1µm for the nerve fiber layer. The mean choroidal thickness was 301.5 ± 34.0µm. Multivariable analysis revealed that the thickness of ARLs had a significant negative correlation with AL (β=−0.20, p < 0.001) and a significant positive correlation with body height (β=0.11, p = 0.04), with males having a greater retinal thickness than females (β=−0.22, p < 0.001). Foveal thickness was significantly positively correlated with body height (β=0.13, p = 0.02) but not with AL (β=0.11, p = 0.06) or sex (β=−0.04, p = 0.55). Conclusion The structures of the retina and choroid in 8-year-old Japanese children were associated with several factors, but the associations varied by retinal site and layer.